Secondary azoospermia after sleeve gastrectomy: a case report - Gricelda Gomez, M.D., M.P.H; Alexandra Berger, M.D; Martin Kathrins, M.D (Elsevier, 2021)
Objective: To report the first case of secondary azoospermia after sleeve gastrectomy. Design: Case report. Setting: Academic male infertility clinic. Patient(s): A 33-year-old man with secondary azoospermia and primary testicular failure with testosterone deficiency after laparoscopic sleeve gastrectomy. Intervention(s): Hormonal therapy with anastrozole for 10 months and diagnostic testicular biopsy. Main Outcome Measure(s): Semen analyses and testicular histopathology. Result(s): Non-obstructive azoospermia persisted at 20 months after surgery despite hormonal therapy with anastrozole. Testicular histopathology revealed the presence of Sertoli cells only. Conclusion(s): Although further research is need to determine the relationship between sleeve gastrectomy and secondary infertility, men should be informed of the potentially deleterious effects of this surgery on semen parameters.